LCST polymers: Thermoresponsive nanostructured assemblies towards bioapplications - Pasparakis, George; Tsitsilianis, Constantinos (Polymer (Guilford), 2020)
Thermoresponsive polymers constitute an important class of materials for biomedical application due to their thermally reversible coil-to-globule transition which can be exploited in a multitude of biomedical applications spanning from triggered drug delivery systems in the form of bulk hydrogels and nanoparticles, “smart” cell culture setups, sensors and actuators, and separation technologies. In this perspective article we present the basic physicochemical properties of poly (N-isopropylacrylamide) (PNIPAM), which is the most widely studied thermoresponsive polymer with a lower critical solution temperature. We describe the basic thermodynamic and physicochemical parameters that affect the LCST and present selective applications that utilize thermoresponsive polymers in the form of nano-assemblies including micelles, polymersomes, microcapsules and microgels, as well as injectable hydrogels for biomedical applications. [Display omitted] •Thermoresponsive polymers and their key properties in aqueous media are presented.•The lower critical solution temperature and the factors affecting it in aqueous media are described.•T-responsive polymers in the form of micelles, polymersomes, microcapsules, and microgels are discussed.•Injectable thermoresponsive hydrogels with shear thinning properties are introduced for bioapplications.